A study of the Relationship Between Quality and Efficiency of Service in Logistics Company of the Eastern Economic Corridor in Thailand (EECO) - Ulumpananda, Wimonsiri; Kumboon, Buraporn; Sajjanand, Siriporn; Kositkanin, Chonkanok (Journal for Developing the Social and Community, 2022)
The objective of this study was to study the impact of logistics relationship on the quality and efficiency of logistics services of Eastern Economic Corridor companies; (1) To study the level of quality of logistics services of private companies operating in the Eastern Economic Corridor area. (2) To study the efficiency of logistics services of private companies operating in the Eastern Economic Corridor area. (3) to analyze the relationship of quality and efficiency of logistics services of private companies operating in the Eastern Economic Corridor area. This research considers the content of this study focusing on logistics activities of private companies, operating in the Eastern Economic Corridor, can be divided into two main parts which consist of; The independent variable is the logistics relationship of the Eastern Economic Corridor Company. The dependent variable which is considered to be divided into 2 subvariables are; service efficiency variables, and service quality variables. Data were obtained by using a questionnaire tool from a sample of 312 people, and by interviewing 15 people. An exploratory component analysis was performed to group the indicators of the metrics obtained from the empirical data by significant KMO and Bartlett Test of Sphericity values ​​and should be greater than 0.8, indicating that the collected data can factor Analysis. The confirmatory components were then analyzed to group the theoretical variables together with the structural equation modeling. The results of the study found that the quality components of logistics services of private companies operating businesses, the efficiency of logistics services of private companies that do business, and the logistics relationship of private companies operating in the Eastern Economic Corridor area, having complete concepts and theory elements. The component level of logistics relationship to the quality and efficiency of logistics services was found. There are three components at the highest level: Reliability dimension (mean= 4.35), Tangibles (mean=4.33), and Select Partners (mean= 4.32) respectively. Next are the 5 high-level components, which are: Perform Strategic (mean= 3.84), Response (mean=3.82), Time dimension (mean=3.81), Understanding the Customer (mean= 3.81), and Evaluate Alternative (mean=3.80) respectively. Finally, there are moderately assembled organizations, namely; Structure Operating Model (mean= 3.79), Reliability (mean= 3.79), Security (mean=3.78), Assessment (mean=3.77), Decision to Form Relationship (mean=3.77), Implementation and Continuous Improvement (mean=3.76) , and Cost Management dimension (mean=3.75) respectively.